INTERVENSI MODIFIKASI PERILAKU (TOKEN EKONOMI) PADA ANAK CONDUCT DISORDER - Junita Sipahelut (IAKN Ambon, 2019)
The subject is a boy aged 15 years and 4 months, experiencing a conduct disorder disorder. This study aims to reduce conduct disorder by using behavior modification techniques with token economy. Data collection techniques, observation, interviews and personality tests. The intervention consisted of one family counseling session and six behavior modification sessions. After the intervention, the subject's family understood the information conveyed by the therapist, and there were several changes in the subject's behavior. This is supported because the subject's mother can change her attitude towards the subject and there is moral support from the teacher at school so that the subject feels accepted by the family and teachers at school.